MecA gene and methicillin-resistant Staphylococcus aureus (MRSA) isolated from dairy farms in East Java, Indonesia - Sancaka Chasyer Ramandinianto; Aswin Rafif Khairullah; Mustofa Helmi Effendi (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Ramandinianto SC, Khairullah AR, Effendi MH. 2020. MecA gene and methicillin-resistant Staphylococcus aureus (MRSA) isolated from dairy farms in East Java, Indonesia. Biodiversitas 21: 3562-3568. Milk Borne Disease (MBD) can be caused by a variety of pathogenic bacteria, one of which is Staphylococcus aureus which has a large impact on aspects of public health. The therapy used to treat staphylococcal infection is Oxacillin preparations that can inhibit bacterial wall synthesis, but the adaptation of the mecA gene to staphylococcal cassette chromosome mec (SCCmec) causes the emergence of strains of methicillin-resistant S. aureus (MRSA). The purpose of this study was to detect the level of MRSA strain contamination in dairy cows in East Java by comparing the mecA gene, Oxacillin, and Cefoxitin Disc Diffusion Methods and Oxacillin Resistance Screen Agar (ORSA) detection methods. A total of 150 cow's milk samples were taken at 3 village dairy farms in East Java, samples were added to the enrichment media Buffer Pepton Water (BPW) and then isolates were planted and purified using Mannitol Salt Agar (MSA). The detection of MRSA was carried out by the Kirby Bauer disc diffusion preparation Cefoxitin 30 ?g and Oxacillin 30 ?g then confirmed by ORSA and the presence of mecA gene by the polymerase chain reaction (PCR) method. The results showed that from a total of 92 S. aureus isolates using Oxacillin disc test, 24 resistant isolates were obtained, using Cefoxitin disc test, 17 isolates were obtained, and using the ORSA test 18 MRSA isolates were obtained. MRSA isolates tested by PCR obtained evidence of 2 isolates of mecA gene. It can be concluded that the Oxacillin disc test was the highest sensitivity for detecting MRSA strain isolate, however, mecA gene was the golden standard to detect MRSA on the dairy farms.